LENGTH OF GRAVITY OF THE MARE OF THE BOSNIAN MOUNTAIN BREED - Žiga, Enver; Rustempašić, Alma (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Throughout the centuries the Bosnian Mountain Horse was the mainstay of the communities that lived in the mountainous regions of the former Yugoslavia, therefore, the breeding of this horse was widespread throughout the parts where the conditions of life were harsh, and where the carrying of heavy loads and the transport of people was difficult due to the terraine. From the very beginning of the selective breeding process (that started during the beginning of the 19th Century) the big question was always for how long would the mare be in foal. The stockman were constantly interested in how to roughly predict the day that the foal would be born. There were few scientific works that covered this topic, but in our research we have discovered that that the length of gestation is 337.45 days this is slightly different to the previous understanding.